Surface Reconstruction and In Situ Formation of 2D Layer for Efficient and Stable 2D/3D Perovskite Solar Cells. Issue 12 (5th November 2021) - Deng, Chunyan; Wu, Jihuai; Du, Yitian; Chen, Qi; Song, Zeyu; Li, Guodong; Wang, Xiaobing; Lin, Jianming; Sun, Weihai; Huang, Miaoliang; Huang, Yunfang; Gao, Peng; et al.
Abstract: The 2D/3D composite structure possesses both the excellent stability of 2D perovskite and the excellent performance of 3D perovskite, which recently have attracted special attention. Different from the popular isopropanol, a novel additive solvent—polypropylene glycol bis (2‐aminopropyl ether) (A‐PPG) is introduced here to dissolve excess PbI2 and perovskite, and then reconstruct and in situ form the quasi‐2D perovskite layer on 3D perovskite bulk. The lone electron pairs of the ether‐oxygen and amino in A‐PPG can form coordination bonds with Pb 2+ . The introduction of A‐PPG tunes the energy array of functional layers, passivates defects, and mitigates carrier nonradiative recombination. Consequently, the 2D/3D perovskite device exhibits a championship efficiency of 22.24% with a distinguished open‐circuit voltage of 1.21 V (the thermodynamic limit of 1.30 V). Moreover, the 2D/3D device still maintains 90% of the original efficiency in the ambient atmosphere with a relative humidity of 30 ± 10% after 50 days. Abstract : A multifunctional molecule of polypropylene glycol bis (2‐aminopropyl ether) is introduced to reconstruct and in situ form the quasi‐2D perovskite layer on 3D perovskite bulk, which tunes the energy array of functional layers, passivates defects and mitigates carrier recombination, and improves the stability of the device. Consequently, the 2D/3D perovskite device exhibits an improved efficiency of 22.24% with a distinguished open‐circuit voltage of 1.21 V.